Study on Agrivoltaic System for Interaction Among Crop Production and Solar Photovoltaic Power Generation: AGRIVOLTAIC SYSTEM FOR CROP PRODUCTION AND POWER GENERATION - Modi, Vinit; Vishal Singh; Surendra Poonia (Annals of Arid Zone, 2024)
The concept of Agrivoltaics, combining agriculture and solar photovoltaic system, is ideal for populous countries like India as it provides access to eco-friendly power and crop production from the same land. The main objective of this study was to evaluate the performance of solar photovoltaic strings and their suitability for agricultural practices for the green gram crop under North-Gujarat agro-climatic conditions. Eight equal-capacity strings with different geometry were designed to evaluate power generation and crop production beneath the strings. The experiment involved eight strings taken as eight treatments and the traditional system of green gram growing was considered as the ninth treatment. Results revealed that treatment-1 (3.2 m) height string with continuous solar panel pattern) provided the highest gross income from power generation and green gram yield (Rs. 24364.00). In terms of net realization, treatment-4 (1.82 m) string with continuous solar panel pattern) provided the highest net return of Rs. 12417.00, as the capital cost was less for the system. Treatment-5, which involved transparent panels, was found to be better for the photosynthesis process of the green gram crop, as it provided the highest yield under the agrivoltaic system